(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Thrombocytopenia is the major sign of dengue fever; many times patients require ICU admission when platelet count severely goes down in view of bleeding tendency. Aim: To compare the effect of kiwi and guava in thrombocytopenia induced by dengue fever or any other viral fever. Methods and Materials: A randomized clinical trial performed at Vishwaraj Hospital Pune, Maharashtra, India from July 2022 to September 2022 after registration done under the Clinical Trials Registry- India with clinical trial registration number CTRI/2022/07/043922 & approval by Institutional Ethics Committee.100 thrombocytopenia patients induced by dengue selected by randomization method, in which 50 patients in kiwi group who received green kiwi fruit and 50 patients in guava group who received white flesh guava fruit.